Informing the Nursing Professional Development Scope and Standards: Exploring Current and Future Nursing Professional Development Practice Through a World Café Methodology. Issue 3 (May 2021) - Maloney, Patsy; Harper, Mary G.
Abstract : A two-phase research study was conducted to inform the upcoming fourth edition of Nursing Professional Development: Scope and Standards of Practice . This column describes Phase 1, which used a virtual world café methodology to gather qualitative data from 32 nursing professional development experts. Eighteen themes emerged from the data supporting the six responsibilities of the nursing professional development practitioner. Researchers found the virtual world café to be a useful technique for eliciting expert opinions.